Afrocuban religions in Sara Gomez's one way or another and Gloria Ronaldo's Oggun - Ebrahim, Haseenah (The Western Journal of Black Studies, 1998)
This paper explores the depiction of Afrocuban religions in two films - Sara Gomez's One way or another(1974/1977) and Gloria Rolando's Oggun: Forever present(1991).A (Western) feminist's analysis of Gomez's One way or another characterizes Abakua and Santeria as "voodoo" - not only collapsing three different Afro-Carribean religious traditions, but also reflecting Marxistbiases that exclude (ironically) a recognition that Gomez's depictions of Abakua and Santeria reflect a gendered perspective.Rolando's Oggun reflects a recent trend in Cuban cinema to celebrate Afrocuban religious practices.Oggun's stunning visuals, compelling song and dance sequences, and fascinating mythology provoke a desire to understand the role and impact of this remarkable religious tradition in Cuban society.
Volume.22, No.4.